Book Review: A. Hajiyev. Mythopoetics of the Russian Prose: 2nd Half of the 20th Century (2018) - D. B. Tereshkina (Научный диалог, 2019)
The review of the monograph by doctor of philology Asif Hajiyev, Professor of the “Azerbaijan” University (Azerbaijan Republic), devoted to the theory and practice of mythological poetics in Russian prose of the second half of the XX century is presented. The subject, structure of the book, the main observations of the author of the reviewed work, the methods used and the style of presentation are characterized.